The Role of Feed Restriction on DNA Methylation, Feed Efficiency, Metabolome, Biochemical Profile, and Progesterone Patterns in the Female Filial Generation (F1) Obtained From Early Feed Restricted Ewes (F0) - Andrés, Sonia; Madsen, Ole; Montero, Olimpio; Martín, Alba; Giráldez, F. Javier (Frontiers in Physiology, 2021)
Deficient management of replacement animals in the farm during early developmental windows may promote adverse programming effects on reproductive traits and subsequent transmission to the next generation. In this sense, DNA methylation profiles allow researchers to decode epigenetic regulation mechanisms in mammals and identify novel candidate genes correlated with phenotype differences in both, dams and offspring. Therefore, improving knowledge in the field of epigenetics and inter-generational effects caused by pre- and postnatal early nutritional events (e.g., feed restriction) is crucial for refining strategies dedicated to animal breeding. In the present study we determined differences in the global blood methylation patterns, biochemical profile and metabolome of ewe lambs (F1) born from either early feed restricted dams (F0-RES) or fed ad libitum (F0-ADL). Our data show that functional categories such as those related to cellular processes, phosphorylation, nervous system, immunity response or reproductive function were enriched significantly in the F1-RES lambs due to differences in the methylation of genes in these categories. These F1-RES lambs did not show differences in feed efficiency during the replacement period but presented higher levels of insulin and triglycerides and reduced concentration of progesterone, whereas the metabolome profile demonstrated variations in the bile acid composition when compared to the F1-ADL lambs. Taken together all these results suggest that inter-generational effects caused by early feed restriction of dams (F0) may persist in the F1 female lambs with negative consequences on genes involved in cellular processes and reproductive traits.